Changes in microbiome composition during ontogeny and dispersal of the coral boring sponge Thoosa mismalolli - Eric Bautista-Guerrero; José Luis Carballo; Fabián Alejandro Rodríguez Zaragoza; Bruno Goméz-Gil; Alejandra García-Gasca; Alma P. Rodríguez-Troncoso; Adrián González-Castillo (Scientific Reports)
Abstract Dispersal is an important life history trait that plays a key role in the demography and evolution of species. We employed a combined approach of DNA sequencing and transmission electron microscopy to examine the changes in the microbiome during the ontogeny and dispersal of the coral-excavating sponge Thoosa mismalolli. The results show that sponge can acquired their associated bacteria via both vertical (VT) and horizontal transmission (HT). Adult sponges, brooding larvae, and early free-swimming sponge larvae harbor a similar high-diversity microbial assemblage, dominated by Proteobacteria and Chloroflexi, which change throughout the larval dispersal phase. Larvae collected offshore showed a reorganization of their microbiome with a significant reduction of the dominance of inherited bacteria (Proteobacteria and Chloroflexi), and an enrichment of environmentally derived bacteria taxa (Bacteroidetes, Tenericutes, and Firmicutes). TEM confirmed a substantial change in cell structure and microbial composition, attributed to symbionts’ massive phagocytosis. This research provides information on microbiome dynamics through the sponge ontogeny and sheds on their possible role in the dispersal capacity of their larvae.